Agrarian Kentucky - Clark, Thomas D. (The University Press of Kentucky, 2015)
For subsistence farmers in eastern Kentucky, wealthy horse owners in the central Bluegrass, and tobacco growers in Western Kentucky, land was, and continues to be, one of the commonwealth's greatest sources of economic growth. It is also a source of nostalgia for a people devoted to tradition, a characteristic that has significantly influenced Kentucky's culture, sometimes to the detriment of education and development. As timely now as when it was first published, Thomas D. Clark's classic history of agrarianism prepares readers for a new era that promises to bring rapid change to the land and.